An SFL-based model for investigating explicitation-related phenomena in translation - Othman, Waleed (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
This paper proposes a model for investigating explicitation, implicitation, and explicitness in translated texts. The paper highlights the need to distinguish clearly between explicitation and other kinds of translation shifts. Specifically, when comparing target text (TT) renderings with the corresponding source text (ST), the model does not assume correspondence between shifts (and non-shifts) in ideational content and explicitation status. Nor does it assume correspondence between the overall explicitation status of renderings and the explicitness of the TT as a whole from the perspective of the relevant register in the target language (TL). The model draws on systemic functional linguistics to develop procedures for a three-phase analysis of these different explicitation-related phenomena. The parameters of traceability, realisational congruency and delicacy are applied to determine explicitation status, seen as arising from choices made by the translator within the systemic potential of the TL. Explicitness is determined from the perspective of registerial instantiation by comparing frequencies of different types of rendering with those found in a comparable corpus of TL non-translations. A case study, in which the model is applied to an English-to-Arabic translation of manner of motion verbs in a literary genre, demonstrates how each phase yields new insights, from a different perspective, while providing input for comparative analysis of the choices available in the two language systems with regard to the linguistic feature of interest.